Effect of Point Sampling Density in Quantifying Mouse Lung Emphysema. Issue 3 (9th December 2014) - Limjunyawong, Nathachit; Kearson, Alexandra; Das, Sandhya; Mitzner, Wayne
ABSTRACT In the official joint policy document of the American Thoracic Society and European Respiratory Society (Hsia et al., Am J Respir Crit Care Med 181:394‐418), the need for proper stereologic assessment of lungs was emphasized. In this document it was emphasized that for the quantitative analysis of lung histologic sections, one of the most robust and reliable methods is point and intercept counting (Knudsen et al., J Appl Physiol 108:412‐421). One of the practical aspects of this method is how many points or intercepts are needed. The answer to this question has been considered from a theoretical perspective, and it depends on the relative magnitudes of the methodological and biologic variabilities. Although it is generally accepted that in a normal lung, one needs only 100–200 points to sufficiently lower the methodological variability, given the increased variability often seen in experimental emphysematous lung injury, the requisite number of points of intercepts has not been evaluated. In this study, we examined this question by focusing on some of the relevant sampling levels in mice with extensive elastase‐induced emphysema. Using fixed samples of tissue blocks, we varied the number of sampling points or intercepts from about 25 to 1, 000 in control and emphysematous lungs. Our results show that, at the sampling levels investigated, even with the increased heterogeneity in the lung tissue damage caused by elastase, the number of sampling points needed to detect changes is similar to what is needed for control mice. Anat Rec, 298:531–537, 2015. © 2014 Wiley Periodicals, Inc.